At Least Two Genes Encode Many Variants of Irak3 in Rainbow Trout, but Neither the Full-Length Factor Nor Its Variants Interfere Directly With the TLR-Mediated Stimulation of Inflammation - Rebl, Alexander; Rebl, Henrike; Verleih, Marieke; Haupt, Stephanie; Köbis, Judith M.; Goldammer, Tom; Seyfert, Hans-Martin (Frontiers in Immunology, 2019)
The interleukin-1-receptor-associated kinase 3 (IRAK3) is known in mammals as a negative feedback regulator of NF-B-mediated innate-immune mechanisms. We identified in RNA-seq experiments a prototypic 1920-nt sequence encoding irak3 from rainbow trout (Oncorhynchus mykiss) and 20 variants hereof, which vary in length and nucleotide composition. Based on the DNA-sequence information from two closely related irak3 genes from rainbow trout and an irak3-sequence fragment from Atlantic salmon retrieved from public databases, we elucidated the underlying genetic causes for this striking irak3 diversity. Infection of rainbow trout with a lethal dose of Aeromonas salmonicida enhanced the expression of all variants in liver, head kidney and peripheral blood leucocytes. We analysed the functional impact of the full-length factor and selected structural variants by overexpressing them in mammalian HEK-293 cells. The full-length factor enhanced the basal activity of NF-κB, but did not dampen the TLR2-signalling-induced levels of NF-κB activtion. Increasing the basal NF-B-activity through Irak3 does apparently not involve its C-terminal domain. However, more severely truncated factors did not influence NF-κB activities at all. The TLR2-mediated stimulation did not alter the spatial distribution of Irak3 inside the cells. In salmonid CHSE-214 cells, we observed that the Irak3-splice variant expressing prominently the C-terminal domain quenched significantly the stimulation-dependent production of interleukin-1 and interleukin-8 but not of other immune regulators. We conclude that the different gene and splice variants of Irak3 from trout play distinct roles in the activation of immune-regulatory mechanisms.